Avaliação da performance de fundos de pensão - Lousanne Cavalcanti Barros (2003)
The objective of this empirical study is to evaluate the performance of Brazilian pension funds, verifying if the greater funds can obtain better returns in the changeable revenue in relation to the market, for the period of 1999 to 2001. Thus, for first sub period (04/99 to 03/00) with exception of two entities, all could show good performances. However, as the second sub period (04/00 to 03/01) got negative returns for IBOVESPA, it was difficult to evaluate the performance of these. Even though, two great entities could surpass all the oscillations in this sub period, presenting ability of timing for the market. Over all, the analysis of the data demonstrates that, based on the changeable revenue wallet, the greatestpension funds cannot stand out in relation to the minor funds, even taking higher risks.